Bantengan Arts Development Planning Model in Malang Raya - Sopanah, Ana; Sulistyan, Riza Bahtiar; Rusdianti, Imanita Septian; Supriyadi, Mohammad; Khasanah, Midhatul (TGO Journal of Community Development, 2026)
This activity aims to strengthen the organizational capacity of the Bantengan Galogo Djati art association in Malang Raya through structured mentoring activities. The method used consists of three stages, namely preparation, implementation, and evaluation, which will be carried out from October to November 2025. The preparation stage results in a clearer management structure and a systematic work plan. The implementation stage provides organizational management training, simulation of art activities, and strengthening coordination between members so that the quality of performances increases. Evaluations are carried out to assess the effectiveness of mentoring, identify successes and obstacles, and prepare recommendations for improvement. The results of the activity show an increase in organizational capacity, the formation of a funding strategy, and the opening of opportunities for collaboration with external parties. The discussion emphasized that mentoring plays an important role in maintaining the sustainability of the Bantengan tradition while opening up development opportunities through digitalization and cross-sector cooperation networks. Thus, this activity supports previous research on the importance of organizational planning in the preservation of traditional arts, as well as making a real contribution to the development of culture and creative economy in Malang Raya.